Structural changes in skeletal muscles in hypokinesia and physical loading in the posthypokinetic period of recovery of rats’ organisms - S. L. Popel’ (Regulatory Mechanisms in Biosystems, 2017)
This article reports the study of histo-ultrastructural changes of different structural components of the direct muscle of the thigh of sexually mature male rats over a prolonged period of hypokinesia and subsequent application of physical loading of average aerobic power. Using a light optical, electron microscope (for the exposure of structural transformations of muscle components) and histochemical (for determination of activity of succinate dehydrogenase according to the Nahlas method to identify muscle fibers with different phenotypes) methods, we studied the structural manifestations of adaptation of muscle fibres under prolonged (240 day) hypokinesia and 15–30 episodes of physical loading of average aerobic power in the posthypokinetic period among 55 sexually mature rats. Under prolonged hypokinesis we primarily observed changes in the intramuscular network and morphometric changes in the blood vessels. These data closely correlate with the progression of changes of the subcellular components responsible for energetic and flexible balance of muscle fibres. We found that fast oxygen-glycolytic muscle fibers and their peripheral nervous apparatus are the most sensitive to prolonged hypokinesia. As a result of application of physical loading of average aerobic power, reparative regeneration is intensified, which substantially shortens the period of recovery of structural-functional properties of skeletal muscles in the conditions of hypokinetic disorders. Thus, in prolonged hypokinesia, changes primarily affect the sources of blood supply to skeletal muscles, with the secondary development of reverse processes in muscle fibers and peripheral nervous apparatus with certain morphometric signs.